Factors Associated with Emergency Department Survival of Out-of-Hospital Cardiac Arrest following Traumatic Brain Injury: A Retrospective Cohort Study - Laksanamapune, Thanakorn; Yuksen, Chaiyaporn; Preechanarit, Theeradate; Tienpratarn, Welawat; Leela-amornsin, Sittichok; Jenpanitpong, Chetsadakon; Damdin, Siriporn (Archives of Academic Emergency Medicine, 2026)
Introduction: Traumatic out-of-hospital cardiac arrest (TOHCA) in patients with traumatic brain injury (TBI) is associated with exceptionally poor survival. However, prehospital prognostic factors influencing early survival in this high-risk population remain poorly defined. This study aimed to identify prehospital factors associated with survival to hospital admission among TOHCA patients with TBI in Thailand. Methods: We conducted an 11-year nationwide retrospective cohort study using the Information Technology of Emergency Medicine System (ITEMS), Thailand’s national EMS registry (2012–2022). TOHCA patients with documented TBI who were transported to the emergency department (ED) by emergency medical services (EMS) were included. The primary outcome was survival to hospital admission. Multivariable logistic regression was used to identify independent prehospital factors associated with survival. Results: Of 46,760 TOHCA cases, 22,821 involved TBI, and 16,885 met inclusion criteria with recorded ED outcomes. Overall, 2,872 patients (17.0%) survived to hospital admission. Younger age, longer on scene time, and shorter hospital-to-scene distance were independently associated with improved odds of survival. Several prehospital interventions showed significant benefit, including external bleeding control (adjusted odds ratio (aOR) 1.38, 95% confidence interval (CI): 1.20–1.58), endotracheal intubation (aOR 2.09, 95% CI: 1.69–2.57), intravenous fluid administration (aOR 1.56, 95% CI: 1.24–1.96), and defibrillation (aOR 2.05, 95% CI: 1.66–2.53). In contrast, on-scene time <10 minutes (aOR 0.65, 95% CI: 0.53–0.79) and bone and joint injuries, including closed fractures, open fractures, and dislocations, were associated with reduced survival. Conclusion: Despite the generally poor prognosis of TOHCA patients, particularly those with TBI, our findings demonstrate that adequate on-scene time and the prompt delivery of critical prehospital interventions, including external bleeding control, intubation, hydration, and defibrillation, were independently associated with improved survival to hospital admission.